Improved two-way six-state protocol for quantum key distribution - Shamsul Shaari, Jesni; Ahmad Bahari, Asma' (Elsevier, 2012)
A generalized version for a qubit based two-way quantum key distribution scheme was first proposed in the paper [Phys. Lett. A 358 (2006) 85] capitalizing on the six quantum states derived from three mutually unbiased bases. While boasting of a higher level of security, the protocol was not designed for ease of practical implementation. In this work, we propose modifications to the protocol, resulting not only in improved security but also in a more efficient and practical setup. We provide comparisons for calculated secure key rates for the protocols in noisy and lossy channels.